ANALISIS FAKTOR PENGHAMBAT IMPLEMENTASI REFORMASI BIROKRASI DI BPKAD KABUPATEN KUANTAN SINGINGI - fazly azizi, muhammad (JURNAL KEBIJAKAN PUBLIK, 2025)
Bureaucratic reform is a crucial effort in increasing the effectiveness of public services in Indonesia, especially in the context of regional financial and asset management. One of the agencies that plays an important role in this matter is the Regional Financial and Asset Management Agency (BPKAD) of Kuantan Singingi Regency.The urgency of this research lies in the importance of professional and accountable financial and asset management at the regional level. This research uses the library study method (Library Research) by using literature from books, journals and related scientific articles as the main material for analysis and looking for connections to describe the research problem. The main task and function of government agencies, including the Kuantan Singingi Regency Regional Financial and Asset Management Agency (BPKAD), is to provide services to the community. The formation of government agencies aims to meet community needs, both in terms of quality and quantity of services provided, so as to achieve community satisfaction. Quality, transparent and accountable public services are indicators of successful government performance. Bureaucratic reform is an important step to increase the effectiveness and efficiency of government organizations in providing public services. Ineffective bureaucracy can become an obstacle in achieving the goals of good governance, so changes to the system and a better bureaucratic structure are nedeed.